Sosialisasi Area Rawan Longsor Dan Upaya Mitigasinya Di Kecamatan Lingsar Kabupaten Lombok Barat - Arben Virgota; Baiq Farista; Supardiono Supardiono; Rachmawati Noviana Rahayu; Lalu Adi Gunawan; Lalu Ade Sugiarta; Muhammad Abu Tahsya (Jurnal Gema Ngabdi, 2023)
The Meninting Sub-watershed area, West Lombok Regency is one of the areas prone to landslides. This is due to the topographic conditions of the area which are dominated by very steep slopes. Landslides are one of the disasters that often occur, especially in West Lombok Regency. High rainfall intensity with a long duration is one of the factors causing erosion and landslides on critical slopes. This service activity was carried out with the aim of increasing the knowledge and insight of the community around the Meninting watershed, especially in the Lingsar District, regarding the risk of landslides and mitigation actions that can be taken. The target of this service is the Lingsar District  Government and surrounding communities affected by the landslide disaster. The result of this service activity is an agreement on a follow-up plan for this activity with the Lingsar District and also the affected communities. This agreement is demonstrated by the willingness of the service target community to utilize data and information disseminated in various disaster mitigation and adaptation actions. Mitigation actions that can be taken include mapping areas prone to landslides, controlling land use, improving the quality of infrastructure, education and training and emergency planning. Handling adaptation to landslide disasters can be done by arranging housing, strengthening infrastructure, utilizing technology, increasing community capacity, and sustainable environmental management.